GALERI MURAL DAN GRAFFITI DENGAN PENERAPAN KONSEP EKSPRESI DALAM ARSITEKTUR DI KOTA SURAKARTA - Sudibyo, Brilly Prayudha; Purnomo, MD Edi; Nugroho, Rachmadi (Universitas Sebelas Maret Surakarta, 2016)
Gallery of Murals and Graffiti planning and designing in Surakarta motivated by the issue of urban art, especially murals and graffiti growing in Surakarta. The need for container murals and graffiti that can accommodate, develop, and provide education and information on the value of urban art itself. The existence of Surakarta as a center of art and culture add more motivated issue to planning and designing the Gallery of Murals and Graffiti. The goal is to plan and design a Gallery of Murals and Graffiti that can accommodate the expression of urban art also functions as an alternative public space for the city of Surakarta with the application of the concept of Expression in Architecture. Design issue is how the concept of Expression in Architecture which includes site selection, layout, orientation, circulation, use of material, color selection, and expression forms and facades can be applied to the Gallery of Mural and Graffiti. Design method used is by applying Expression in Architecture and combined with design standards gallery. Application concept of Expression in Architecture on Gallery of Murals and Graffiti such as the design of the site selection, layout, orientation, circulation, use of material, color selection, as well as the shapes and facades expression in building system.